Effect of titanium dioxide on some mechanical, thermal, and surface properties of wood-plastic nanocomposites - Kaymakci, Alperen (BioResources, 2019)
The effects of TiO2 (titanium dioxide) loading were evaluated relative to mechanical, thermal, and surface properties of the wood-plastic nanocomposites (WPNs). Pine wood flour, mixed with maleic anhydride polypropylene (MAPP), TiO2 nanoparticles (0 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, and 5 wt%), and polypropylene, was compounded in a twin screw co-rotating extruder. The mass ratio of the wood flour to polypropylene (PP) was 50/50 (w/w) in all compounds. Test specimens were produced using injection molding machine from the pellets. Flexural and tensile properties, thermogravimetric analysis, surface roughness, wettability, and morphology of the manufactured nanocomposites were evaluated. Flexural and tensile properties of the wood-plastic nanocomposites increased with the increasing content of the TiO2. The surface roughness of the wood-plastic nanocomposites was reduced by increasing the content of TiO2. Increasing the loading of TiO2 increased the amount of residual ash and thermal stability.